Pengaruh Jumlah Penduduk dan Partisipasi Angkatan Kerja terhadap Tingkat Pengangguran Terbuka di Provinsi Sulawesi Tengah Tahun 2010–2023 - Yulia Setiawati Sagiagora; Yulian Rinawaty Taaha; Feliks Arfid Guampe (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Sustainable and targeted development is essential to achieving welfare and economic stability. Central Sulawesi Province faces persistent unemployment issues despite ongoing population growth and changes in labor participation rates. This study examines the influence of population size and labor force participation on the open unemployment rate in Central Sulawesi Province from 2010 to 2023. Using multiple regression analysis and secondary data from the Central Statistics Agency (BPS), the findings show that population size significantly affects open unemployment, while labor force participation has no significant partial effect. However, both variables jointly have a significant impact. The results support economic growth and labor market theories emphasizing the balance between population growth, labor participation, and investment in human capital and technology. The study recommends strengthening job creation policies, improving human resource quality, supporting MSMEs, and enhancing government–private–academic collaboration to align education and training with labor market demands.